Bootleggers and borders : the paradox of prohibition on a Canada-U.S. borderland - Moore, Stephen T. (Stephen Timothy), 1969- (University of Nebraska Press, 2014)
"Between 1920 and 1933 the issue of prohibition proved to be the greatest challenge to Canada-U.S. relations. When the United States adopted national prohibition in 1920--ironically, just as Canada was abandoning its own national and provincial experiments with prohibition--U.S. tourists and dollars promptly headed north and Canadian liquor went south. Despite repeated efforts, Americans were unable to secure Canadian assistance in enforcing American prohibition laws until 1930. Bootleggers and Borders explores the important but surprisingly overlooked Canada-U.S. relationship in the Pacific Northwest during Prohibition. Stephen T. Moore maintains that the reason Prohibition created such an intractable problem lies not with the relationship between Ottawa and Washington DC but with everyday operations experienced at the border level, where foreign relations are conducted according to different methods and rules and are informed by different assumptions, identities, and cultural values. Through an exploration of border relations in the Pacific Northwest, Bootleggers and Borders offers insight not only into the Canada-U.S. relationship but also into the subtle but important differences in the tactics Canadians and Americans employed when confronted with similar problems. Ultimately, British Columbia's method of addressing temperance provided the United States with a model that would become central to its abandonment and replacement of Prohibition. "--